2022
DOI: 10.2147/copd.s368645
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vitamin C Supplementation on Chronic Obstructive Pulmonary Disease (COPD): A Systematic Review and Meta-Analysis

Abstract: Background In recent years, the pleiotropic roles of antioxidants have drawn extensive attention in various diseases. Vitamin C is a well-known antioxidant, and it has been used to treat patients with chronic obstructive pulmonary disease (COPD). This systematic review and meta-analysis aim to demonstrate the impact of vitamin C supplementation in patients with COPD. Methods We searched PubMed, Embase, Cochrane Library, Web of Science, Chinese National Knowledge Infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Similarly, people that use combustible tobacco and consume a diet rich with vitamin C exhibit slower rates of pulmonary decline (FEV 1 ) when compared to those with low vitamin C intake [ 112 ]. This finding was confirmed in patients with COPD, with daily doses of 400 milligrams of vitamin C associated with better lung function (FEV 1 percent predictive and FEV 1 /FVC) [ 15 ], and daily doses of 2 g/day were associated with fewer pulmonary exacerbations over a six-month period [ 113 ]. Additionally, significant improvements in antioxidant capacity and vascular function were also observed in patients with COPD (GOLD stage I–IV) after an acute dose of a combination of vitamin C, vitamin E, and α-lipoic acid [ 114 ].…”
Section: Vitamins a B C And Ementioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, people that use combustible tobacco and consume a diet rich with vitamin C exhibit slower rates of pulmonary decline (FEV 1 ) when compared to those with low vitamin C intake [ 112 ]. This finding was confirmed in patients with COPD, with daily doses of 400 milligrams of vitamin C associated with better lung function (FEV 1 percent predictive and FEV 1 /FVC) [ 15 ], and daily doses of 2 g/day were associated with fewer pulmonary exacerbations over a six-month period [ 113 ]. Additionally, significant improvements in antioxidant capacity and vascular function were also observed in patients with COPD (GOLD stage I–IV) after an acute dose of a combination of vitamin C, vitamin E, and α-lipoic acid [ 114 ].…”
Section: Vitamins a B C And Ementioning
confidence: 89%
“…The role of these vitamins in COPD should be further investigated due to their potential benefits such as reducing oxidative stress [ 122 ] and protecting the airways [ 118 , 119 , 123 ]. In regard to vitamin C, a meta-analysis of ten randomized controlled trials including nearly 500 participants showed a significant improvement in lung function in individuals that supplemented 400 milligrams of oral vitamin C per day [ 15 ]. Additional benefits with fewer pulmonary exacerbations have been described in patients with COPD that received two grams of daily oral vitamin C supplementation [ 113 ].…”
Section: Vitamins a B C And Ementioning
confidence: 99%
See 1 more Smart Citation
“…It helps overcome chronic respiratory disorders. Oxidative stress from toxins and free radicals damages lung tissue, especially in chronic lung disease patients ( Lei et al, 2022 ). Vitamin C protects alveoli and reduces COPD risk ( Lei et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C is recognized as a powerful antioxidant, while vitamin D has the potential to exhibit anti-inflammatory effects. 84 , 85 Although it is currently unclear whether the effectiveness of treating the inflammation response is more effective in the primary disease. There are novel treatment strategies available related to the iron regulatory pathway and hypoxia-inducible factor stabilizers for inflammatory anemia, but their efficacy needs to be further evaluated in clinical trials.…”
Section: Copd and Hematological Diseasesmentioning
confidence: 99%